Observation and measurements of the production of prompt and non-prompt JψJψ mesons in association with a ZZ boson in pppp collisions at s√=8TeVs√=8TeV with the ATLAS detector - Aad, G. (2014)
The production of a Z boson in association with a J/ψ meson in proton-proton collisions probes the production mechanisms of quarkonium and heavy flavour in association with vector bosons, and allows studies of multiple parton scattering. Using 20.3fb−1 of data collected with the ATLAS experiment at the LHC in pp collisions at s√=8TeV, the first measurement of associated Z+J/ψ production is presented for both prompt and non-prompt J/ψ production, with both signatures having a significance in excess of 5σ. The inclusive production cross-sections for Z boson production (analysed in μ+μ− or e+e− decay modes) in association with prompt and non-prompt J/ψ(→μ+μ−) are measured relative to the inclusive production rate of Z bosons in the same fiducial volume to be (36.8±6.7±2.5)×10−7 and (65.8±9.2±4.2)×10−7 respectively. Normalised differential production cross-section ratios are also determined as a function of the J/ψ transverse momentum. The fraction of signal events arising from single and double parton scattering is estimated, and a lower limit of 5.3 (3.7)mb at 68 (95)% confidence level is placed on the effective cross-section regulating double parton interactions.